Time to antibiotic administration and patient outcomes in community-acquired pneumonia: results from a prospective cohort study. (March 2021) - Fally, Markus; Israelsen, Simone; Benfield, Thomas; Tarp, Britta; Ravn, Pernille
Abstract: Objectives: Community-acquired pneumonia (CAP) is a frequently occurring disease linked to high mortality and morbidity. Previous studies indicated that the administration of antibiotics within 4 hrs of admission can improve key patient outcomes associated with CAP, such as mortality and time to clinical stability. However, the results have been heterogeneous and may not be applicable to all healthcare settings. Therefore, we designed a cohort study to estimate the impact of timely antibiotic administration on outcomes in patients admitted with CAP. Methods: The impact of antibiotic administration within 4 hrs of admission and other covariates were estimated for 30-day mortality, stability within 72 hrs, 30-day readmission and time to discharge, using multivariable regression models. Sensitivity analyses were performed on a subset of patients with the most severe CAP and a propensity score matched cohort. Results: In total, 2264 patients were included. Of these, 273 (12.1%) died within 30 days of admission, 1277 (56.4%) were alive and stable within 72 hrs and 334 (14.8%) were discharged alive and readmitted within 30 days. Median length of hospital stay was 5 days (interquartile range 3–8). In all models, the administration of antibiotics within 4 hrs of admission had no significant effect on the outcomes. The adjusted odds ratios (OR) derived from the multivariable models for 30-day mortality, stability within 72 hrs and 30-day readmission were 1.01 (95% confidence interval (CI) 0.76; 1.33), 0.88 (95% CI 0.74; 1.05) and 1.05 (95% CI 0.82; 1.34). The adjusted hazard ratio (HR) for time to discharge was 1.00 (95% CI 0.91; 1.10). Discussion: A strict 4-hr threshold for antibiotic administration in all patients admitted with CAP is not reasonable. Instead, our results suggested that patients should be triaged and prioritized according to age, comorbidities, clinical condition and pneumonia severity.